Durable remission in a patient of mixed phenotype acute leukemia with Philadelphia chromosome-positive treated with nilotinib and lenalidomide: A case report. Issue 14 (April 2018) - Lai, Binbin; Mu, Qitian; Zhu, Huiling; Wang, Yi; Zhang, Yi; Xu, Kaihong; Sheng, Lixia; Ouyang, Guifang
Abstract: Rationale: Philadelphia chromosome-positive mixed phenotype acute leukemia (Ph+ MPAL) is a rare type of leukemia with poor prognosis. Tyrosine kinase inhibitors (TKIs) in combination with chemotherapy have significantly improved its remission rate. However, relapse remains the major obstacle to achieve long survival. Lenalidomide is a second-generation oral immunomodulatory drug that has been broadly applied in the treatment of various hematological malignancies. Patient concerns: A 54-year-old Chinese male patient who complained of chest pain and fatigue for 20 days. Bone marrow aspirate examination revealed hypercellularity with 70% blast cells. Flow cytometry analysis revealed that the blast cells exhibit both myeloid and lymphoid lineage antigens. Chromosomal analysis reveals t(9;22)(q34;q11) translocation. Minor BCR-ABL fusion gene was positive. Diagnosis: Philadelphia chromosome-positive mixed phenotype acute leukemia. Interventions: After relapsed from routine chemotherapy plus imatinib, the therapy was switched to oral therapy with nilotinib and lenalidomide due to his feeble condition. Outcomes: He successfully achieved long survival after oral therapy with nilotinib and lenalidomide. Lessons: Combination of TKIs with lenalidomide may be an effective maintenance treatment regimen for Ph+ MPAL patients with minimal side effect.